Effects of organic acids on the gut ecosystem and on the performance of broiler chickens - ANDREOPOULOU (Μ. ΑΝΔΡΕΟΠΟΥΛΟΥ) M.; TSIOURIS (Β. ΤΣΙΟΥΡΗΣ) V.; GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ) I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Organic acids are studied as candidate alternatives to antibiotic growth promoters. Their action is related to the pH reduction of the intestinal digesta, affecting the gut ecosystem in numerous ways. Intestinal microbiota can be altered as a result of the remarkable antibacterial activity of organic acids and the growth enhancement of non-pathogenic beneficial microorganisms, due to exclusive competition. Antibacterial activity has been widely reported for many poultry pathogens, such as Salmonella spp., Escherichia coli, Clostridium perfringens, Campylobacter spp., both in vitro and in vivo. However, it seems to depend on many factors concerning the weak acid used and the gut ecosystem. Apart from the microbiota, diet supplementation of organic acids has trophic effects on the intestinal mucosa, modifying the morphologic characteristics of intestinal villi and crypts and maintaining epithelial integrity. Furthermore, as found recently, organic acids have anti-inflammatory and immunostimulating properties. Diet acidification increases gastric proteolysis and the utilization of proteins and amino acids, affects pancreatic secretions and mineral absorption. There are also reports for an effect on appetite and palatability of the feed. All these properties attributed to organic acids have either a direct or indirect effect on the performance and health, even though the results presented for poultry lack consistency. Nonetheless, the benefits of organic acids can have practical application in the control of clinical and subclinical conditions, but more research is needed to study these perspectives.